The European Union's Cooperation With Third Countries: Turkey And Libya - Tofig Ismayilzada (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2022)
The European Union has recently been an attractive destination for asylum seekers and migrants. Despite the deadly migration routes, the migration crisis has proved that asylum seekers and migrants are willing to enter European Union territory. The flow of irregular migration to the European Union peaked in 2015. The intensity of migration movement over such a short period raised concerns about internal and external security. At the same time, due to the migration crisis, the European Union intensified its cooperation with third countries on the migration issue. This article first explores the concept of international cooperation on migration and assesses if the selected case studies have any common characteristics to the concept. Second, the paper studies the effectiveness of the European Union's cooperation with Turkey and Libya, which emerged due to the migration crisis. Additionally, the paper provides data to test the effectiveness of cooperation with third countries. The cooperation with Turkey and Libya was an essential tool for the European Union to control its Mediterranean borders. When the consensus was reached, the number of irregular arrivals significantly decreased.